(untitled) (MAUSAM, 2012)
Soybean is a major kharif season crop in parts of M.P., U.P., Gujarat, Punjab and Haryana, Maharashtra, Rajasthan, A.P. and Chattisgarh. The present work was undertaken to study the parameters controlling water requirement of the crop at various phenophases in soybean growing 8 ET- stations (viz., Akola, Bangalore, Banswara, Dharwar, New Delhi, Parbhani, ICRISAT and Rahuri) in various agroclimatic zones. Eight phenophases of the crop (viz., germination, seedling, vegetative, active vegetative, flowering, pod formation, pod maturity and harvesting) were identified. The data were collected for latest available 3 to 5 years and the mean values were analysed. The study on soybean crop revealed that the mean total water requirement demand of the crop varied from 294.7 to 559.2 mm in different soybean growing ET stations. The ET demand reached the peak mostly at active vegetative stage (which was 19.0 to 25.6 % of the total ET demand, at various locations). The computed best – fit ET curves provide ET demand of the crop at any point of the phenophases for the specific location. The rainfall during study period was mostly sufficient to meet the crop specific ET demand at various phenophaes of soybean crop. Abundant soil moisture supported good vegetation cover. The mean Kc value varied widely from 0.61 to 0.98 among different stations studied, which reached their peak mostly at active vegetative to flowering stages, where the values were even more than 1 in most of those phenophases except 3 stations. The mean soybean crop yield and productivity varied widely agroclimatic zone wise. The soybean yield varied from 981.0 kg/ha to 2530.6 kg/ha, while productivity per day varied from 9.0 kg/ha/day to 23.2 kg/ha/day. The WUE of the crop laid between 2.1 kg/ha/mm to 6.0 kg/ha /mm at various locations.